Fabrication and Evaluation of Polyherbal Diaper Rash Gel - Deepak Prashar,; Sakshi Binta,; Niharika,; Pallavi,; Sahil, (Asian Journal of Pharmaceutical Research and Development, 2026)
Diaper rash is a common dermatological condition affecting infants and young children, causing inflammation, discomfort, and potential bacterial or fungal infections. Current synthetic formulations often contain chemical irritants and pose the risk of adverse effects. This research presents the formulation, fabrication, and comprehensive evaluation of a novel polyherbal diaper rash gel incorporating natural botanicals with proven dermatological properties. The gel formulation was developed using Aloe vera (soothing and antimicrobial), Calendula officinalis (anti-inflammatory and wound healing), Chamomilla recutita (calming and protective), and Zinc oxide (protective barrier). The gel was prepared using optimized concentrations of herbal extracts, thickening agents, and preservatives. Physicochemical evaluation included appearance, pH testing, viscosity measurement, spreadability assessment, and antimicrobial activity testing against Staphylococcus aureus and Candida albicans. Stability testing was performed under accelerated conditions (40°C ± 2°C, 75% ± 5% RH for 90 days). The optimized formulation demonstrated excellent physical properties with pH 6.5 ± 0.2, appropriate viscosity for topical application, and superior spreadability. The gel exhibited significant antimicrobial activity against both test organisms, demonstrating MIC values of 62.5µg/mL and 125µg/mL respectively. Stability studies showed consistent physicochemical parameters throughout the testing period. The polyherbal gel formulation presents a safe, efficacious, and cost-effective alternative to conventional diaper rash products, offering dual benefits of soothing relief and antimicrobial protection without adverse effects associated with synthetic ingredients.